Dampening Effects of Perceived Teacher Enthusiasm on Class-Related Boredom in College Students: Longitudinal Mediation Effects of Perceived Task Value - Cui, Guan-yu; Chen, Jing-yi; Wang, Chen; Zhang, Chen; Zhang, Xia; Hu, Yun-jun (Frontiers in Psychology, 2021)
This study aimed to explore the longitudinal mediation effects of college students’ perceived task value between perceived teacher enthusiasm and class-related boredom. We conducted a survey among 1,371 college students from five colleges using the students’ perceived teacher enthusiasm, perception of task difficulty, perception of task value, and class-related boredom questionnaires at two, six, ten, and fourteen weeks of the spring semester; we also surveyed boredom proneness at two weeks. The results showed that after controlling for the effects of boredom proneness and perceived task difficulty, students’ perceived teacher enthusiasm was a significant and longitudinal predictor of class-related boredom. After controlling for the effects of the above control variables, students’ perceived task value played a significant and longitudinal mediating role between their perceived teacher enthusiasm and class-related boredom. The study revealed the mechanism of the mitigating effect of students’ perceived teacher enthusiasm on class-related boredom. Thus, promoting the level of students’ perceived teacher enthusiasm can promote their perception of task value and decrease their class-related boredom.